Training on the Use of Processed Herbal Plants as an Effort to Prevent Degenerative Diseases to the Community - Masfria; Muchlisyam; Reveny, Julia; Syahputra, Hafid (Talenta Publisher, 2023)
This community service aims to increase public knowledge in health and health efforts through promotive and preventive activities by conducting counselling and training in the use of medicinal plants and how to process herbal plants properly and correctly so that people in Ndokum Siroga village, Karo Regency understand the importance of health and a healthy paradigm. by using herbal plants. This community service activity is to increase public awareness of health by introducing a healthy paradigm. The implementation method used is lectures and training where lectures are conducted to increase public knowledge about the health paradigm and the importance of health as well as the introduction of herbal plants to make family medicinal plants while the training is carried out by providing facilities and infrastructure for community service activities to increase community knowledge and skills, including delivery papers on various types of herbal plants used, things to consider in-plant processing, and their properties, as well as the practice of processing plants into drinks that are easy to consume. The conclusion of this activity is very helpful and provides good benefits to the community because this activity can have a direct impact on the community. The analysis technique and activity results are seen from the knowledge of the community before and after the training and counselling by asking questions in an objective form that can describe the different levels of understanding of the participants.